Kajian Erosi Andisol Dibawah Vegetasi Tanaman Kopi, Campuran Kopi dan Kayu Manis, Kayu Manis Serta Hutan di Desa Nilau Dingin - Hasriati Nasution; Yusfaneti; Asmadi Saad (Bulletin of Community Engagement, 2024)
The purpose of the study was to determine the erosion that occurs under coffee, cinnamon, a mixture of cinnamon and coffee and Andisol forest soil. Soil analysis was carried out at the Soil Physics and Chemistry Laboratory, Faculty of Agriculture, University of Jambi. Soil erosion Soil sampling for determining soil erosion in coffee soil, organic matter content, volume weight, total pore space and soil permeability was carried out by survey using the Proportional Random Sampling method in areas planted with coffee vegetation, a mixture of coffee and cinnamon, cinnamon and forest vegetation on a slope of 8% - 15%. The parameters observed were soil organic matter content, permeability, soil volume weight, total pore space, soil erodibility and soil erosion, soil texture. Each treatment was repeated 15 times. To distinguish the physical properties of Andisol under cinnamon, coffee, cinnamon mixed with coffee and forest soil. conducted using the Unpaired Mean Value Test at the 5% level (Steel and Torrie, 1995). From the results of the Unpaired Mean Value Test, it was found that under coffee vegetation and a mixture of coffee and cinnamon, the soil organic matter, permeability, volume weight, total pore space, erodibility and soil erosion were the same, but significantly different from the soil under cinnamon vegetation and forest. Under cinnamon vegetation and forest, there was no significant difference in the parameters of organic matter content, volume weight, total pore space, erodibility and soil erosion and only differed in soil permeability. The conclusion is that soil erosion in coffee vegetation and a mixture of coffee and cinnamon is the same erosion. However, it is different from cinnamon vegetation and forest.